The transcription factor Zfp503 promotes the D1 MSN identity and represses the D2 MSN identity - Shang, Zicong; Yang, Lin; Wang, Ziwu; Tian, Yu; Gao, Yanjing; Su, Zihao; Guo, Rongliang; Li, Weiwei; Liu, Guoping; Li, Xiaosu; Yang, Zhengang; Li, Zhenmeiyu; et al. (Frontiers in Cell and Developmental Biology, 2022)
The striatum is primarily composed of two types of medium spiny neurons (MSNs) expressing either D1- or D2-type dopamine receptors. However, the fate determination of these two types of neurons is not fully understood. Here, we found that D1 MSNs undergo fate switching to D2 MSNs in the absence of Zfp503. Furthermore, scRNA-seq revealed that the transcription factor Zfp503 affects the differentiation of these progenitor cells in the lateral ganglionic eminence (LGE). More importantly, we found that the transcription factors Sp8/9, which are required for the differentiation of D2 MSNs, are repressed by Zfp503. Finally, sustained Zfp503 expression in LGE progenitor cells promoted the D1 MSN identity and repressed the D2 MSN identity. Overall, Zfp503 promotes the D1 MSN identity and represses the D2 MSN identity by regulating Sp8/9 expression during striatal MSN development.